ANALISIS PENGARUH KOMPENSASI DAN KARAKTERISTIK PEKERJAAN TERHADAP KINERJA DENGAN MEDIASI KEPUASAN KERJA ( Studi Pada RSUD Kab Temanggung ) (Students' Journal of Economic and Management, 2013)
This study examinesthe effect of compesation on job satisfaction of employees, examine the effect of job characteristics on job satisfaction of employees, examine the effect of Compesation on Performance, examine job characteristics on Performance and examine Job Satisfaction to Performance. The results showed that the first hypothesis which states that  compesation  have positive and significant influence to job satisfaction of employees, received. The second hypothesis which states that the job characteristics have positive  and a significant influence to job satisfaction of employees, received. The third hypothesis states that compesation is don’t have a significant  relationship of the nurse performance ,rejected .The fourth  hypothesis which states that job characteristics have a positive and significant impact on Nurse Performance, were rejected. The fifth hypothesis which stated that job satisfaction has positive and significant impact on nurse performance. This research also showed that job satisfaction as a mediated variable that effect between compesation to nurse  performance Keywords : compensation, job characteristic , job satisfaction and performance.